Addressing inequality and intolerance in human–wildlife coexistence. Issue 4 (14th May 2020) - Jordan, Neil R.; Smith, Bradley P.; Appleby, Robert G.; van Eeden, Lily M.; Webster, Hugh S.
Abstract: Millennia of human conflict with wildlife have built a culture of intolerance toward wildlife among some stakeholders. We explored 2 key obstacles to improved human–wildlife coexistence: coexistence inequality (how the costs and benefits of coexisting with wildlife are unequally shared) and intolerance. The costs of coexisting with wildlife are often disproportionately borne by the so‐called global south and rural communities, and the benefits often flow to the global north and urban dwellers. Attitudes and behaviors toward wildlife (tolerance versus intolerance) vary with social and cultural norms. We suggest more empathetic advocacy is needed that, for example, promotes conservation while appropriately considering those who bear the costs of conflict with wildlife. To achieve more equitable cost‐sharing, we suggest limiting the costs incurred by those most affected or by sharing those costs more widely. For example, we advocate for the development of improved wildlife compensation schemes, increasing the scale of rewilding efforts, and preventing wildlife‐derived revenue leaching out of the local communities bearing the costs of coexistence. Abstract : Article Impact Statement : Reduce coexistence inequality and intolerance by prioritising local economies, smarter compensation schemes, rewilding and empathetic advocacy. Abstract : Soluciones para la Desigualdad y la Intolerancia en la Coexistencia Humano – Fauna Resumen: Los milenios de conflicto entre los humanos y la fauna han construido una cultura de intolerancia hacia la fauna entre algunos actores. Exploramos dos obstáculos importantes para la mejora de la coexistencia humano – fauna: la desigualdad de coexistencia (cómo los costos y los beneficios de la coexistencia con la fauna están compartidos de una manera desigual) y la intolerancia. Los costos de coexistir con la fauna generalmente están asumidos de manera desproporcional por las llamadas comunidades del sur global o rurales, y los beneficios de convivir con la fauna generalmente fluyen hacia el norte mundial y hacia los habitantes de zonas urbanas. Las actitudes y comportamientos hacia la fauna (tolerancia versus intolerancia) varían con las normas culturales y sociales. Sugerimos la necesidad de una defensa más empática que, por ejemplo, promueva la conservación a la vez que considera de manera apropiada a aquellos que asumen los costos del conflicto con la fauna. Para lograr costos compartidos más equitativos sugerimos limitar los costos incurridos por aquellos más afectados o compartir los costos de manera más amplia. Por ejemplo, abogamos por el desarrollo de esquemas mejorados de compensación de fauna, el incremento de la escala de los esfuerzos por el retorno a la vida silvestre y la prevención del secuestro de ingresos derivados de la fauna fuera de las comunidades locales que asumen los costos de la coexistencia.